KETERAMPILAN SEPAKBOLA Studi Korelasional Antara Persepsi Kinestetik, Adaptasi Dan Kelincahan Dengan Keterampilan Sepakbola Siswa-siswa Sekolah Sepakbola Di Kota Bandung - Hendrayana, Yudy (Program Studi Pendidikan Manajemen Perkantoran, 2011)
The purpose of this research is to study the relationship between kinesthetic perception,adaptation, and agility with football skills. This research has been conducted at football schools(SSB) with a sample 40 students selected randomly.The research concludes that there arepositive correlation between : (1) kinesthetic perception and football skills (2) adaptation andfootball skills, (3) agility and football skills (4) kinesthetic perception, adaptation, and agilitywith football skills. The findings give an implication that football skills could be increased byimproving kinesthetic perception, adaptation, and agility .